2018
DOI: 10.1111/1475-6765.12286
|View full text |Cite
|
Sign up to set email alerts
|

The opinion‐policy nexus in Europe and the role of political institutions

Abstract: Abstract.A strong link between citizen preferences and public policy is one of the key goals and criteria of democratic governance. Yet, our knowledge about the extent to which public policies on specific issues are in line with citizen preferences in Europe is limited. This article reports on the first study of the link between public opinion and public policy that covers a large and diverse sample of concrete public policy issues in 31 European democracies. The findings demonstrate a strong positive relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 72 publications
1
63
0
1
Order By: Relevance
“…Passive "coalitions" in the form of lobbying camps favoring the same policy outcome (Baumgartner et al 2009;Klüver 2013;Mahoney and Baumgartner 2015) can be identified based on gathering the positions of all active actors on an issue. To enable the present study, an online survey was sent to 1,410 active advocates on 50 policy issues as part of the GovLis Project on government responsiveness 2 (Rasmussen, Mäder, and Reher 2018; see also Flöthe and Rasmussen 2019; Junk and Rasmussen 2019; Rasmussen and Reher 2019; Rasmussen, Reher, and Toshkov 2019;Romeijn 2018). Capturing, in addition to these, active cooperation between actors requires collecting even more information, some of which is private, as coalitions do not always leave traces.…”
Section: Method: Capturing Active Lobbying Coalitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive "coalitions" in the form of lobbying camps favoring the same policy outcome (Baumgartner et al 2009;Klüver 2013;Mahoney and Baumgartner 2015) can be identified based on gathering the positions of all active actors on an issue. To enable the present study, an online survey was sent to 1,410 active advocates on 50 policy issues as part of the GovLis Project on government responsiveness 2 (Rasmussen, Mäder, and Reher 2018; see also Flöthe and Rasmussen 2019; Junk and Rasmussen 2019; Rasmussen and Reher 2019; Rasmussen, Reher, and Toshkov 2019;Romeijn 2018). Capturing, in addition to these, active cooperation between actors requires collecting even more information, some of which is private, as coalitions do not always leave traces.…”
Section: Method: Capturing Active Lobbying Coalitionsmentioning
confidence: 99%
“…Capturing, in addition to these, active cooperation between actors requires collecting even more information, some of which is private, as coalitions do not always leave traces. To enable the present study, an online survey was sent to 1,410 active advocates on 50 policy issues as part of the GovLis Project on government responsiveness 2 (Rasmussen, Mäder, and Reher 2018; see also Flöthe and Rasmussen 2019;Junk and Rasmussen 2019;Rasmussen, Reher, and Toshkov 2019;Romeijn 2018). This survey collected information on issue-specific "signaling coalitions," meaning coalitions that jointly campaigned in public or concertedly approached policy makers.…”
Section: Method: Capturing Active Lobbying Coalitionsmentioning
confidence: 99%
“…Building on the recent literature about the effect of political institutions on dynamic representation (Hobolt and Klemmensen 2008;Rasmussen et al 2018;Soroka and Wlezien 2015;Wlezien and Soroka 2012), the article analysed whether and how specific characteristics of the party system moderate the sanction-policy link from the perspective of citizens. The sixth round of the European Social Survey collects data from 25 democracies showing a very high degree of systemic variation in terms of number of parties and levels of party polarization or volatility.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative research on representation, conceptualized as both congruence and dynamic representation, emphasizes the role of institutions in shaping citizens' perceptions although evidence about this effect is not entirely clear. These studies are mostly focused on decentralization, concentration of powers and, above all, electoral systems to analyse, in particular, the effect of disproportionality on cabinet size (Hobolt and Klemmensen 2008;Powell 2000Powell , 2011Rasmussen et al 2018;Soroka and Wlezien 2015;Wlezien and Soroka 2012). Nevertheless, the potential effect of the party system on dynamic representation has been less investigated, although Wlezien andSoroka (2012, p. 1425) stress that 'there are other political institutions to consider as well, including party systems themselves'.…”
Section: Explaining Variation In Citizens' Perceptions: the Impact Ofmentioning
confidence: 99%
See 1 more Smart Citation